Disambiguation of tonally unspecified Mandarin syllables - Huff, C; Payne, E (International Speech Communication Association, 2012)
The interpretation of written Mandarin monosyllables presented in tonally unspecified pinyin was investigated for 22 native speakers. Results showed a preference for high relative lexical frequency and, to a lesser extent low homophone density candidates, with some interaction between these two factors: where one candidate in a homophone cohort had a particularly high frequency, cohort density was found to play little or no role in selection. Where the frequency of the two most frequent candidates was comparable, characters from lower density tonal homophone cohorts were preferred. These results indicate a strong role for relative lexical frequency and, through the weaker homophone density effect a lesser role for tone, in Mandarin homophone disambiguation.